Compromiso organizacional y satisfacción laboral de los empleados de la cooperativa de ahorro y crédito Maquita. - Cujilema Mangia, Wilson Paul (2023)
Organizational commitment is a very important topic in different organizations, for it refers to the degree to which an employee identifies with the organization, as well as the desire to stay and be part of it. On the other side, work satisfaction is a factor that reflects the emotional state of workers with their work environment, as these two variables are key elements for an organization that seeks success. This research searches for the relationship between organizational commitment and work satisfaction inside the Savings and Credit Cooperative Maquita, through the use of instruments that allowed us to collect information. The objective of this study was to determine the relationship between the two variables. The methodology used was quantitative, descriptive and correlational, and two instruments were applied: One to identify the organizational commitment of the authors Allen and Meyer (1990) composed of 24 questions divided into 3 dimensions and the instrument implemented to define job satisfaction S20/23 of the authors Meliá and Peiró (1998) which includes 5 dimensions and consists of 23 questions giving a total of 47 questions implemented to 88 employees. SPSS and Microsoft Excel 2019 were used to obtain statistical analyses of reliability and correlation, and a correlation was demonstrated between the two variables studied. It was concluded that there is an influence on the employees' commitment to work satisfaction. Finally, the Chi-Square calculation was performed, which demonstrated the dependence between the two variables.